Menilai Kesehatan Keuangan Perusahaan Properti Serta Memahami Faktor-Faktor Utama pada Emiten BEI (2020-2024) - Wati, Indi Rakhma; Indriasih, Dewi; Susetyo, Budi (Jambura Economic Education Journal, 2026)
This study focuses on detecting financial distress in property and real estate companies listed on the IDX for the period 2020 - 2024 with the role of agency cost, company size, financial performance, and capital structure. Using a quantitative approach and data from 51 companies selected through purposive sampling techniques, this study aims to evaluate how these various factors interact with each other and affect the financial state of the company. Agency cost is measured to understand how costs arising from conflicts of interest between management and shareholders can negatively impact financial stability. The study found that company size has a positive influence on financial distress, suggesting that larger companies tend to face higher financial risks. On the other hand, profitability, liquidity, and leverage have not been shown to have a significant effect on financial distress. Another important finding is that capital structures dominated by debt contribute to an increased risk of financial distress. The research provides valuable insights for investors and stakeholders in the property sector, as well as highlights the importance of efficient financial management to prevent more serious financial problems.